Hubungan Pola Makan, Stres, dan Kualitas Hidup dengan Kejadian Dispepsia Fungsional pada Pasien di IGD RS. Rizani Paiton - Moh. S. Guntur; Iin Aini Isnawati; Dodik Hartono (STIKes Ibnu Sina Ajibarang, 2023)
Dyspepsia is a collection of symptoms related to various gastrointestinal disorders, including nausea, vomiting, bloating, upper abdominal pain, feelings of fullness in the upper abdomen, and early satiety. This study aims to determine the Relationship Between Dietary Patterns, Stress, and Quality of Life with the Incidence of Functional Dyspepsia in Patients at the Emergency Department of Rizani Hospital, Paiton.The research utilized an analytical correlational design with a cross-sectional approach, involving a sample of 32 respondents selected through accidental sampling technique.The findings of this study revealed that respondents had a category of poor dietary patterns in 19 cases (59.4%), had a moderate level of stress in 18 cases (56.2%), had a very good quality of life in 18 cases (56.2%), and had a history of dyspepsia in 17 respondents (53.1%).The Chi-Square analysis results indicated a significance value of α<0.05 for dietary patterns (0.000), stress level (0.000), and quality of life (0.004), signifying a Relationship Between Dietary Patterns, Stress, and Quality of Life with the Incidence of Functional Dyspepsia in Patients at the Emergency Department of Rizani Hospital, Paiton. The results of logistic linear regression analysis showed an Exp(B) value of 0.657 for dietary patterns, signifying that among the three factors, dietary patterns were the most dominant factor.Integrating the research findings into patient care procedures and guidelines can enhance patient care by considering dietary patterns, stress management, and quality of life. If you have a history or symptoms of functional dyspepsia, consider seeking medical advice from qualified healthcare professionals. Proper treatment and symptom management can improve your quality of life.and increase the number of samples so that the results of the study are maximized .